Evaluation of Baseline Hematologic Parameters of Steady State Sickle Cell Disease Patients at The Chantal Biya’s Foundation, Yaounde- Cameroon (International Journal of Scientific Research and Management (IJSRM), 2019)
Introduction Sickle cell disease is a genetic abnormality involving the hemoglobin. Although it is primarily a red blood cell disorder, the white blood cells and platelets are also affected by the mutation. The consequence hemoglobin S causing polymerization of hemoglobin, results in hemolysis and anemia. This study aims to provide baseline hematologic parameters in steady state sickle cell disease patients compared with the reference values of normal healthy subjects used at the Chantal Biya Foundation (CBF), in order to monitor other sicklers in Cameroon. Methodology A comparative analysis of sickle cell hematologic parameters with control hematologic parameters of normal healthy subjects (reference values of healthy subjects used at the Chantal Biya Foundation) was carried out. Results A total of 62 sickle cell disease patients in steady state who complied with the selection criteria were recruited. Of the 62, 29 were females and 33 were males. The age range was from 1 year to 19 years and an average age of 6 ± 4.19 SD. Results from sickle cell patients showed an increase in white blood cells (WBCs), neutrophils and lymphocytes and a great decrease in the mean values of hematocrit Hct. as well as RBC indices, but no great or slight difference in the values of basophils compared with the reference values of normal healthy subjects in the CBF Yaoundé, 2015. Conclusion Sickle cell disease patients in steady state have lower values of red cells parameters, but higher values of white cells and platelets count when compared with the reference values of normal healthy subjects used at the Chantal Biya Foundation.